Proton imaging of an electrostatic field structure formed in laser-produced counter-streaming plasmas. (March 2016) - Morita, T.; Kugland, N. L.; Wan, W.; Crowston, R.; Drake, R. P.; Fiuza, F.; Gregori, G.; Huntington, C.; Ishikawa, T.; Koenig, M.; Kuranz, C.; Levy, M. C.; et al.
Abstract: We report the measurements of electrostatic field structures associated with an electrostatic shock formed in laser-produced counter-streaming plasmas with proton imaging. The thickness of the electrostatic structure is estimated from proton images with different proton kinetic energies from 4.7 MeV to 10.7 MeV. The width of the transition region is characterized by electron scale length in the laser-produced plasma, suggesting that the field structure is formed due to a collisionless electrostatic shock.